2021
DOI: 10.1186/s12885-021-08591-0
|View full text |Cite
|
Sign up to set email alerts
|

Integration of RNA-Seq and proteomics data identifies glioblastoma multiforme surfaceome signature

Abstract: Background Glioblastoma multiforme (GBM) is a highly lethal, stage IV brain tumour with a prevalence of approximately 2 per 10,000 people globally. The cell surface proteins or surfaceome serve as information gateway in many oncogenic signalling pathways and are important in modulating cancer phenotypes. Dysregulation in surfaceome expression and activity have been shown to promote tumorigenesis. The expression of GBM surfaceome is a case in point; OMICS screening in a cell-based system identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The major advantage of RNA-seq is providing the sequence of low abundance species and quantitative data, as the sequencing reads frequency represents the abundance of genes in the population. 20 However, the complex nature of biological systems, the lack of data availability, and the need for experimental validation can limit the effectiveness of bioinformatics approaches. Therefore, it is important to use bioinformatics tools in combination with other approaches to ensure the identification of viable and effective targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major advantage of RNA-seq is providing the sequence of low abundance species and quantitative data, as the sequencing reads frequency represents the abundance of genes in the population. 20 However, the complex nature of biological systems, the lack of data availability, and the need for experimental validation can limit the effectiveness of bioinformatics approaches. Therefore, it is important to use bioinformatics tools in combination with other approaches to ensure the identification of viable and effective targets.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput technologies, including microarray gene expression and next-generation sequencing, are powerful and cost-effective technologies that provide the possibility for comprehensive identification and prioritization of GESPs with therapeutic potential in cancers. The major advantage of RNA-seq is providing the sequence of low abundance species and quantitative data, as the sequencing reads frequency represents the abundance of genes in the population 20 . However, the complex nature of biological systems, the lack of data availability, and the need for experimental validation can limit the effectiveness of bioinformatics approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Complex GB organoids (GBO) cultures were first gathered from multiple cell types derived from primary patient tumors to reflect their heterogenicity [ 227 ]. Neoplastic cerebral organoids (neoCOR) were developed via genetically manipulating cerebral organoids to induce GB growth [ 228 ]. Later, cerebral organoid GB co-cultures (GLICO) were generated from patient GSCs co-culturing with brain organoids to reflect the tumor–brain interactions [ 229 ].…”
Section: Other Therapeutic Approaches In Gbmentioning
confidence: 99%
“…[49][50][51][52][53] FCGR2A, CYBB, CXCL8 and ITGB2 were significantly upregulated in GBM and associated with shorter overall survival of GBM patients. [54][55][56][57][58] As for the role of CCR1 in GBM, the results are still controversial. Zhang et al found that CCR1 and CCR5 were two key receptors of CCL8 and they triggered CCL8-induced invasion of GBM cells, 59 while Pham et al reported that individual deletion of CCR1 or CCR5 had little or no effect on the survival of tumor-bearing mice, or the number of GBM-infiltrated microglia/macrophages and lymphocytes.…”
Section: Dovepressmentioning
confidence: 99%